2009
DOI: 10.1051/0004-6361/200912350
|View full text |Cite
|
Sign up to set email alerts
|

Probing X-ray irradiation in the nucleus of NGC 1068 with observations of high-Jlines of dense gas tracers

Abstract: Context. Single-dish observations of molecular tracers have suggested that both star formation and an AGN can drive the gas chemistry of the central ∼kpc of active galaxies. The irradiation by UV photons from an starburst or by X-rays from an AGN is expected to produce different signatures in molecular chemistry, which existing data on low-J lines cannot distinguish, as they do not trace gas at high temperature and density. Depending on the angular scale of a galaxy, the observed low-J lines can be dominated b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 37 publications
7
42
3
Order By: Relevance
“…Others have been assuming smaller source sizes such as 1. 5 (Pérez-Beaupuits et al 2009), but we have found that a smaller source size does not significantly change our results for the physical conditions of the CND. For the rest of this paper, we will be focusing on high-density tracer emission from the CND, but first we find it appropriate to comment on the most prominent feature of our spectrum, 12 CO J = 2 → 1, mostly from the SB ring.…”
Section: Spectrum Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Others have been assuming smaller source sizes such as 1. 5 (Pérez-Beaupuits et al 2009), but we have found that a smaller source size does not significantly change our results for the physical conditions of the CND. For the rest of this paper, we will be focusing on high-density tracer emission from the CND, but first we find it appropriate to comment on the most prominent feature of our spectrum, 12 CO J = 2 → 1, mostly from the SB ring.…”
Section: Spectrum Resultscontrasting
confidence: 58%
“…Several recent studies indicate that the CND of NGC 1068 is an XDR (Usero et al 2004;Pérez-Beaupuits et al 2009;Krips et al 2008;Garcia-Burillo et al 2010). There are a variety of diagnostics of XDR/PDR environments that can be utilized with millimeter-range molecular transitions.…”
Section: Introductionmentioning
confidence: 96%
“…For simplicity we restricted H 2 densities to lie within the same range values explored for SiO. Pérez-Beaupuits et al (2009), based on a multi-transition CN analysis, have derived a more restricted density range (n(H 2 ) = 10 6±1 cm −3 ), which nevertheless lies within the range explored here. In the first scenario we need about an order of magnitude increase in n(H 2 ) to fit the progression of ratios from low-velocities to high-velocities (see Fig.…”
Section: Sio Abundancesmentioning
confidence: 96%
“…By contrast, current gas-phase XDR models successfully reproduce the SiO abundances derived in NGC 1068 without resorting to dust grain chemistry. Nonetheless, the inclusion of dust grain chemistry, likely linked to the mechanical heating of the molecular ISM, would help solve the controversy regarding the abundances of species like HCN and HNC, under-predicted by XDR schemes Loenen et al 2008;Pérez-Beaupuits et al 2009). Actually, while CN is overly produced in gas-phase XDR models, HCN is under-produced with respect to the level required by observations in AGNs.…”
Section: X-ray Chemistry In Ngc 1068mentioning
confidence: 99%
“…As mentioned before, we initiate the molecular cloud with turbulent conditions that are typical for an active environment, FWHM = 5 km s −1 , or σ turb = 2.1 km s −1 (Pérez-Beaupuits et al 2009), and apply this over all scales with a power spectrum of P(k) ∝ k −4 , following the empirical laws for compressible fluids (Larson 1981;Myers & Gammie 1999;Heyer & Brunt 2004). This scaling is also known as Burgers turbulence (Burgers 1939;Bec & Khanin 2007).…”
Section: Initial Conditionsmentioning
confidence: 99%